Simultaneous determination of eight metabolites of organophosphate and pyrethroid pesticides in urine. Issue 1 (2nd January 2017) - Guo, Xin Y.; Sun, Li S.; Huang, Meng Y.; Xu, Wei L.; Wang, Ying; Wang, Na
ABSTRACT: A simultaneous method for quantifying eight metabolites of organophosphate pesticides and pyrethroid pesticides in urine samples has been established. The analytes were extracted using liquid–liquid extraction coupled with WCX solid phase extraction (SPE) cartridges. Eight metabolites were chemically derivatized before analysis using gas chromatography–tandem mass spectrometry (GC–MS–MS). The separation was performed on a HP-5MS capillary column (30 m × 0.25 mm × 0.25 µm) with temperature programming. The detection was performed under electro-spray ionization (ESI) in multiple reaction monitoring (MRM) mode. An internal standard method was used. The extraction solvent, types of SPE cartridges and eluents were optimized by comparing the sample recoveries under different conditions. The results showed that the calibration curves of the five organophosphorus pesticides metabolites were linear in the range of 0.2–200 μg/L ( r 2 ≥ 0.992) and that of the three pyrethroid pesticides metabolites were linear in the range of 0.025–250 μg/L ( r 2 ≥ 0.991). The limits of detection (LODs, S/N ≥ 3) and the limits of quantification (LOQs, S/N ≥ 10) of the eight metabolites were 0.008–0.833 μg/L and 0.25–2.5 μg/L, respectively. The recoveries of the eight metabolites ranged from 54.08% to 82.49%. This efficient, stable, and cost-effective method is adequate to handle the large number of samples required for surveying the exposure level of organophosphorus and pyrethroid pesticides in the general population.